Conceptual Analysis on the Potential Regulation of Income Tax Incentives for Floating Hospital’s Financing by State-Owned Enterprises - Adrianto Dwi Nugroho; Regina Ditta Prameswari Bismark (Universitas Negeri Semarang, 2023)
This study aims to explore the possibility of tax facility to encourage financing of floating hospitals in Indonesia by state-owned enterprises. This research combines juridical and empirical methods by using data collected from questionnaire, interview, and literature studies. This study finds that income tax facility in the form of deduction of donation made for floating hospitals from taxable income of state-owned enterprises could increase their interests in financing operating expenses of floating hospitals. In formulating the facility, the Ministry of Health should communicate with the Ministry of Finance to expand the scope of tax allowance to include floating hospitals as social infrastructure or to qualify donations made specifically to improve accessibility of health facilities in certain regions.